f ( x ) = − 2 x 3 − 9 x 2 − 1 2 x + 6
What is the maximum value of f ( ∣ x − 2 ∣ ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
we have f ( x ) = − 1 1 x 3 − 1 2 x + 6 , if x → ∣ x − 2 ∣ f ( ∣ x − 2 ∣ ) = − 1 1 ∣ x − 2 ∣ 3 − 1 2 ∣ x − 2 ∣ + 6
To Find f M a x ( ∣ x − 2 ∣ ) , i will Differentiate the function and equate it to 0 .
\color{#333333}{f^{'}(|x-2|)=-33|x-2|^2\dfrac{x-2}{|x-2|}-12\dfrac{x-2}{|x-2|}+0 = 0 \\ \implies \dfrac{x-2}{|x-2|}\bigg{(}33|x-2|^2+12\bigg{)}=0\\ \implies \dfrac{x-2}{|x-2|}=0 \\ \text{Now observe that , } \lim_{x\to 2^{+}}\dfrac{x-2}{|x-2|}=1 \text{ and } \lim_{x\to 2^{-}}\dfrac{x-2}{|x-2|}=-1 }
which means that at x = 2 function is maximum , f ( 0 ) = 6 is our answer
Wonderful approach! Thank you for the solution.
Problem Loading...
Note Loading...
Set Loading...
The maximum value of f ( ∣ x − 2 ∣ ) is identical to the maximum value of f ( ∣ x ∣ ) as it is just a horizontal translation.
f ( ∣ x ∣ ) = − 1 1 ∣ x ∣ 3 − 1 2 ∣ x ∣ + 6 . Since ∣ x ∣ ≥ 0 for all x , and f ( ∣ x ∣ ) will decrease as ∣ x ∣ increases, the maximum value of the function is found when ∣ x ∣ = 0 .
f ( 0 ) = 6